Modulasi Pola Fermentasi Rumen dan Emisi Gas Metana dari Penambahan Ekstrak Lerak pada Silase Gamal (MODULATION OF RUMEN FERMENTATION AND METHANE EMISSION BY LERAK EXTRACT ADDITION TO GLIRICIDIA SILAGE) - Yuliana, Pristian; Laconi, Erika Budiarti; Jayanegara, Anuraga; Achmadi, Suminar Setiati; Samsudin, Anjas Asmara (Jurnal Veteriner, 2019)
This study aimed to evaluate the effects of lerak fruit extract (Sapindus rarak) addition to leguminous gamal silage (Gliricidia sepium) on methane emission, rumen fermentation pattern, and rumen microbial population in vitro. In vitro rumen fermentation was designed according to a randomized complete block design with four replicates and consisted of 3 treatments, i.e. (1) gamal silage without lerak extract addition, (2) gamal silage + lerak extract 2% (w/w), and (3) gamal silage + lerak extract 4% (w/w). The measured parameters were chemical composition, saponin content, gas production, ammonia, methane, volatile fatty acid (VFA), and rumen microbial population. Results showed that the addition of 4% lerak extract increased gas production after 24 and 48 h, increased organic matter digestibility of gamal silage, increased propionate and decreased methane emission as compared to control treatment (P<0.05). Addition of lerak extract tended to reduce methanogen population and total protozoa in the rumen in vitro. Lerak extract at level 2% significantly increased ammonia concentration (P<0.05). It can be concluded that the addition of lerak extract at level 4% to gamal silage can increase gas production, organic matter digestibility and proportion of propionate, reduce methane emission, and tend to reduce metanogen population and total protozoa in the rumen in vitro.